2005
DOI: 10.1111/j.1464-410x.2005.05692.x
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal shock wave lithotripsy with a transportable electrohydraulic lithotripter: experience with >300 patients

Abstract: OBJECTIVETo review a multicentre experience of using a transportable lithotripter (STS-T, Medstone, Inc, Aliso Viejo, CA. USA) for treating patients with urolithiasis in all parts of the urinary tract. PATIENTS AND METHODSIn all, 326 patients with a total of 370 stones were treated as outpatients with the STS-T lithotripter. All patients received a single shock wave lithotripsy treatment and were followed after 4-6 weeks in the outpatient clinic, the primary endpoint being to determine the efficacy (as defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Furthermore, the efficacy of ESWL is very dependent on the skills of the technician performing the treatment and in the present study treatments were carried out by a small team of very skilled and dedicated technicians [ 8 ]. In a previous multicentre study it was demonstrated that a transportable ESWL system had a high margin of safety with low complications rates and no apparent sacrifice of efficacy with regard to non-transportable systems [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the efficacy of ESWL is very dependent on the skills of the technician performing the treatment and in the present study treatments were carried out by a small team of very skilled and dedicated technicians [ 8 ]. In a previous multicentre study it was demonstrated that a transportable ESWL system had a high margin of safety with low complications rates and no apparent sacrifice of efficacy with regard to non-transportable systems [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results show that SLX-F2 is effective in fragmenting solitary stones throughout the urinary tract. The overall stone-free rate of 76.3% and EQ of 0.64 are acceptable, particularly when compared with other electromagnetic and newer generation lithotripters [14][15][16][17][18][19][20][21][22][23][24] (Table 5). It could be argued that to obtain good results we selected our patients, but comparing the results achieved with various lithotripsy units at various institutions is difficult, if not impossible, due to variability in patient selection, definition of success, follow-up methods and the reported use and classification of auxiliary procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Of all patients treated at our institution with the Modulith SLX-F2 lithotripter from September 2004 to August 2006, we selected 233 (mean age 51 years; 172 males and 61 females) with either symptomatic solitary renal (group A, 170, mean diameter 15.5 mm, range [8][9][10][11][12][13][14][15][16][17][18][19][20] or ureteric stones (group B, 63, mean diameter 9.5 mm, range [5][6][7][8][9][10][11][12][13][14][15]. Exclusion criteria from the study were: PUJ obstruction, multiple stones, stone diameter > 2 cm, stones in a lower calyx with unfavourable anatomy (considering the following factors: angle between the pelvis and the lower calyx; infundibulum diameter and length), active infection, and impacted ureteric stones (defined as the one with hydroureteronephrosis up to the stone and no visualization of the ureter below it, and no changes in stone location during the last 2 months).…”
Section: Methodsmentioning
confidence: 99%